1990
DOI: 10.1161/01.res.67.2.510
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein messenger RNA in rat arteries and veins.

Abstract: Glandular kallikrein (EC 3.4.21.8) belongs to a subgroup of serine proteases coded by a multigene family. A kininogenase resembling glandular kallikrein has been identified in vascular tissue; however, it is not clear whether it is synthesized by vascular tissue or taken up from plasma. To determine the potential for kallikrein synthesis in vascular tissues, we tested whether messenger RNA (mRNA) for glandular kallikrein is present in rat arteries and veins. Poly(A+) RNA was isolated from pools of arteries or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 30 publications
2
43
0
1
Order By: Relevance
“…We found evidence that mRNA for glandular kallikrein is present in an established rat vascular smooth muscle cell line 12 ; in addition, Oza et al 13 recently reported that vascular smooth muscle cells in culture release kallikrein. In preliminary work, we found that vascular kininogenase activity is still present after removal of the endothelium by collagenase treatment.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…We found evidence that mRNA for glandular kallikrein is present in an established rat vascular smooth muscle cell line 12 ; in addition, Oza et al 13 recently reported that vascular smooth muscle cells in culture release kallikrein. In preliminary work, we found that vascular kininogenase activity is still present after removal of the endothelium by collagenase treatment.…”
Section: Discussionsupporting
confidence: 50%
“…Because plasma contains glandular kallikrein, 7 -8 vascular kininogenase activity could be due to trapped plasma; however, this is unlikely, as extensive washing did not remove the kininogenase from the vessel wall. We found messenger RNA (mRNA) for glandular kallikrein in rat vascular tissue, 12 suggesting that the kininogenase activity was due to locally synthesized glandular kallikrein. We used SBTI to inhibit the possible kinin-generating activity of plasma kallikrein or trypsin-like enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…However, even though the 5′ and 3′ flanking regions are highly homologous among the various genes, their regulation and site of expression are different, suggesting that small variations in the nucleotide sequence of the 5′ region can have a significant influence on gene expression. While the kallikrein gene is expressed mainly in the submandibular gland, pancreas and kidney, we detected small amounts of kallikrein mRNA in the heart, vascular tissue, and adrenal glands on polymerase chain reaction (PCR) (189,237). Kallikrein and similar enzymes have been found in the arteries and veins (190), heart (188), brain (58), spleen (57), adrenal glands (255), and blood cells (189); they have also been observed in the pituitary gland (66,216), pancreas (84), large and small intestines (242,320), and salivary and sweat glands (106) along with their exocrine secretions.…”
Section: Introductionmentioning
confidence: 93%
“…The kallikrein-kinin system in the vasculature and regulation of local blood flow-Arteries and veins contain a kallikrein-like enzyme, and both vascular tissue and smooth muscle cells in culture contain kallikrein mRNA (190,237). Vascular smooth muscle cells in culture release both kallikrein and kininogen (200).…”
Section: The Kallikrein-kinin System In Inflammationmentioning
confidence: 99%
“…We have reported that vascular tissue contains a kininogenase that has the same properties as glandular kallikrein 9 and that messenger RNA for kallikrein is present in vascular tissue and smooth muscle cells in culture. 10 Oza et al n reported that vascular smooth muscle cells in culture release both kallikrein and kininogen (kallikrein substrate). Thus, it may be that vascular kininogenase generates kinins continuously and that they are rapidly destroyed by peptidases such as EP-24.15 and ACE.…”
mentioning
confidence: 99%